It Is Not All Because of Socialism — On East-West Differences and Their Origins - Sascha O. Becker; Lukas Mergele; Ludger Wößmann (Wirtschaftsdienst)
Abstract Even on the 30th anniversary of German unity, there is still a lot of talk about East-West differences. Typically, these differences are attributed to different political systems, which have created different impressions. As a result of the division of Germany in 1949 into the GDR and the Federal Republic as well as the reunification in 1990, a lively interest in the social sciences has developed as they offer a unique framework for analysing the effects of communism. Never before has such an unexpected introduction and abolition of a communist regime occured on the territory of a previously and subsequently united country. This paper looks into the history of East-West differences and argues that the division and reunification of Germany are nonetheless not a simple “experiment” from which one can directly deduce the effects of communism. The paper finds that the populations of East and West Germany already differed before the division, that the GDR and FRG were unequally affected by the Second World War, and that selective East-West migration took place during the division. Nevertheless, the remaining East-West differences are not necessarily permanent.